A Model of Local Potential-Based Fashion Production Units for Troso Woven Fabrics - Putri, Firta Firdauzia; Widjanarko, Dwi; Syamwil, Rodia (Journal of Vocational and Career Education, 2018)
The development of a local potential-based fashion production unit requires the integration between the national curriculum and local values. This study aims (1) to find a model of local potential-based fashion production units for troso woven fabrics; (2) to test the validity of the local potential-based fashion production unit model for troso woven fabric; and (3) to test the effectiveness of the local potential-based fashion production unit model for troso woven fabrics. The research and development (R & D) design was employed in this study. The production unit management model developed in this study was a local potential-based management model by involving students not only in service unit but also in their management so that they can improve the competence of sewing and entrepreneurship. The results of the production unit model at Vocational High School 2 Jepara, Central Java, Indonesia showed that the model that has been validated by experts is very valid using the Critical Validity Ratio (CVR) all items get a value of 1 with a condition of 0.99 for 2 experts, so that according to the CVR, all items were categorized valid. The results of the limited trial also showed that the fashion production unit model was considered effective, which resulted from student's t-test with a significance of 0.001 <0.05. This indicated that the model could improve the competence of sewing and entrepreneurial competence of the students. The results of the local potential-based fashion production unit model of troso woven fabric were also seen from changes in student attitudes in entrepreneurship which are assessed by self-confidence, responsibility, leadership spirit, communication and enthusiasm in seeking business opportunities and increasing local potential. In addition to being able to become a reference in carrying out the activities of the production unit, the model can provide experience and entrepreneurial skills to students.